2012
DOI: 10.3354/meps09942
|View full text |Cite
|
Sign up to set email alerts
|

Comparative behavior of red lionfish Pterois volitans on native Pacific versus invaded Atlantic coral reefs

Abstract: Pacific red lionfish Pterois volitans have invaded Atlantic reefs and reached much greater population densities than on native reefs. We hypothesized that lionfish on invaded reefs would (1) experience higher kill rates and thus spend less time hunting, given the naïveté of Atlantic prey, (2) consume a greater variety of prey, given the lack of native prey defenses, and (3) display less pronounced crepuscular patterns of hunting, given the ease of capturing Atlantic prey. Comparative behavioral observations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 43 publications
4
65
0
Order By: Relevance
“…In this work an ontogenetic lionfi sh diet composition variation was found, with crustaceans as the more abundant/important prey for small specimens, whereas as lionfi sh grows the more abundant/important prey were found to be fi sh. These results are similar to other studies that also reported a relation between sizediet in lionfi sh (Cure et al 2012). Many reef fi sh species use seagrass and mangrove as juvenile habitat (Mumby et al 2006).…”
Section: Discussionsupporting
confidence: 91%
“…In this work an ontogenetic lionfi sh diet composition variation was found, with crustaceans as the more abundant/important prey for small specimens, whereas as lionfi sh grows the more abundant/important prey were found to be fi sh. These results are similar to other studies that also reported a relation between sizediet in lionfi sh (Cure et al 2012). Many reef fi sh species use seagrass and mangrove as juvenile habitat (Mumby et al 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Live Paleomonetes varians (Leach 1814) (Grass shrimp) were chosen as trial prey and supplied from Seahorse aquariums. This species was selected to represent a generic prey species and since juvenile lionfish predate largely on invertebrates rather than fish (Cure et al 2012) and due to the successful use of Paleomonetes spp. (Cerino et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…ambush predation, cooperative hunting, palpation, herding, and directed water-jets) (Kendall 1990, Morris & Akins 2009, Albins & Lyons 2012, lionfish consume large quantities and a broad diversity of juvenile and small-bodied adult reef fish as well as small invertebrates (Morris & Akins 2009). Prey naïveté in the invaded range, along with the lionfishes' resemblance to more benign organisms, also appears to contribute to their hunting success (Cure et al 2012). Considering these feeding characteristics, their rapid growth rate (Edwards et al 2014), small size-at-maturity (Morris 2009, Gardner et al 2015, high fecundity and high spawning frequency (Morris 2009, Gardner et al 2015, and apparent lack of natural predators (Albins & Hixon 2013), there is great concern that if their populations are not properly managed, invasive lionfish could cause significant ecological disruption in Bermuda, through predation and resource competition.…”
Section: Introductionmentioning
confidence: 99%